The Effect of Problem-Based Learning Model on Student Learning Outcomes in Mathematics Subjects in Grade III of SDN 2 Biskang - Manik, Roima Sartina; Tanjung, Darinda Sofia; Silalahi, Eka Kartika; Silaban, Patri Janson; Gaol, Rumiris Lumban; Loh, Aaron Loh (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to determine the effect of the Problem-Based Learning model on third-grade students' mathematics learning outcomes at SDN 2 Biskang in the 2024/2025 academic year. This study uses a quantitative method and a pre-experimental research design. The population in this study consists of all third-grade students at SDN 2 Biskang. The sample was taken using non-probability sampling, specifically a convenience sampling, in which the population served as the sample, consisting of 23 third-grade students. To determine the students' initial abilities, the researcher administered a pretest with an average score of 59.69, which was categorized as poor. After the researcher applied the Problem-Based Learning model, students' learning outcomes improved, with an average score of 81.26, indicating good performance. This research can be supported by the correlation coefficient of 0.960, which indicates that rhitung (0.960) ≥ rtabel (0.184), so Ha is accepted. Thus, the Problem-Based Learning model strongly influences the learning outcomes of third-grade students at UPTD SPF SD Negeri 2 Biskan. As seen from the t-test results, 3.783 ≥ 2.080, indicating that Ha is accepted. This shows a significant positive influence of the Problem-Based Learning model on the learning outcomes of third-grade students at SDN 2 Biskang for the 2024/2025 academic year.